Follicle-stimulating hormone and blood lead levels with bone mineral density and the risk of fractures in pre- and postmenopausal women - Tong, Huixin; Su, Bo; Liu, Zhize; Chen, Yongjie (Frontiers in Endocrinology, 2022)
Background The conclusions on the associations of serum follicle-stimulating hormone (FSH) and blood lead levels with bone mineral density (BMD) were controversial. Furthermore, little was known on the impacts of co-existence of serum FSH and blood lead levels on BMD and the risk of fractures in premenopausal and postmenopausal women. Therefore, the present study aimed to examine the associations of serum FSH and blood lead levels with BMD and the risk of fractures in premenopausal and postmenopausal women. Methods Data were derived from the National Health and Nutrition Examination Survey. FSH is assayed using the Microparticle Enzyme Immunoassay technology. Blood lead levels were measured using atomic absorption spectrometry. BMD was measured using dual energy X-ray absorptiometry. Fractures were defined as subjects with fractures in any site of hip, wrist, and spine. Results This study included 3798 participants. Elevated blood lead levels were associated with increased serum FSH levels (β= 48.22, 95% CI: 40.21~ 56.22). Serum FSH levels were negatively associated with total femur BMD in pre- and postmenopausal women. However, elevated serum FSH levels were associated with a lower lumbar spine BMD and a higher risk of fractures only in postmenopausal women (β= -0.0010, 95% CI: -0.0015~ -0.0006; OR: 1.007, 95% CI: 1.000~1.014, respectively). Conclusions Serum lead levels were associated with serum FSH levels. Serum FSH levels were associated with a lower BMD and a higher risk of fractures.